Incidence and infestation by Varroa destructor (Mesostigmata – Varroidae) in Africanized Apis mellifera in hives of Alto Villa Victoria, Satipo - Alomía Lucero, José (2024)
The objective was to assess the incidence and infestation percentage of the mite Varroa destructor mite under natural field conditions in apiaries managed among coffee plants, shaded by Inga edulis trees. The study was carried out in December at an altitude of 1,502 m above sea level. Sampling involved 9 randomly selected hives out of 25, from which 100 bees were taken as a sample from each hive, these bees were submerged in a 70-degree ethanol solution in a container; all bees die and float, but the mites remain at the bottom of the container for counting and then calculating the corresponding percentage. The results show that 55.56% tested positive for the presence of V. destructor in the hives, while 44.44% tested negative; an average of 1.65% + 2.58% V. destructor infestation was found in the total number of Africanized bee hives evaluated; while the average infestation in infested hives is 2.96+2.91%. These averages are considered low.